Ferulenol, a Sesquiterpene Coumarin, Induce Apoptosis via Mitochondrial Dysregulation in Lung Cancer Induced by Benzo[a]pyrene: Involvement of Bcl2 Protein - Lariche, Nesrine; Lahouel, Mesbah; Benguedouar, Lamia; Zellagui, Ammar (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Ferulenol, a sesquiterpene coumarin, was extracted from “Ferula vesceritensis” and possesses pro-oxidative and anticancer effects in different types of cancer. Objective: The objective of this study is to determine whether ferulenol has an anticancer effect by regulation the Bcl2 protein expression in lung cancer induced by benzo[a]pyrene in Wistar rats. Methods: Rats in group 1 have received, intraperitoneally, olive oil and considered as controls, animals of group 2 were treated with 100 mg/kg of benzo[a]pyrene intraperitoneally in order to induce lung cancer for 24 weeks, the 3rd groups of rats received the ferulenol 50 mg/kg intraperitoneally after 24 weeks of administration of benzo[a]pyrene and the last group, the rats were treated with ferulenol alone 50 mg/kg. Results: Treatment with ferulenol significantly increased the rate of lipid peroxidation and decrease enzymatic (CAT and GST) and non-enzymatic (GSH) anti-oxidants in benzo[a]pyrene induced lung cancer. Anticancer efficacy of ferulenol was evaluated by down-regulation of Bcl2 protein and up-regulation of Bax protein, Therefore, ferulenol can alter the functionality of lung mitochondria by increasing the production of superoxide anion and mitochondrial swelling. Conclusion: Together, our results depict that ferulenol can be used as pro-oxidant and chemotherapeutic agent against lung cancer.
Keywords: lung cancer